Descomplicando a menopausa: website de informações e apoio as mulheres - Caldeira, Maria Socorro de Albuquerque (2021)
Objectives: Identify the relationship between climacteric expression and psychosocial factors. Presenting ways that can improve coping with this phase of a woman's life. Method: An integrative review was carried out, which provided an understanding of how climacteric and menopause factors could influence women's quality of life. From this, a retrospective field research with a quantitative approach was carried out with elderly women, where the most prevalent symptoms during climateric/menopause were investigated and the association of these symptoms with perceptions of symptoms and quality of life was analyzed using inferential statistics. Based on the results found, a website was created as a space for information and exchange of experiences. Results: In the integrative review, 12 primary studies were selected that pointed to somatovegetative and urogenital symptoms and anxiety/depression disorders as most frequently reported during menopause. In the field study, the profile of the sample was characterized by women aged 55 to 64 years (50.5%), white (64.9%), Catholic (63.1%), married (59.5%), with children (84.7%), with higher education level (87.4%), retired (57.7%), menopause for more than five years (73.0%). Hypertension was the most prevalent chronic disease (33.3%) and although elderly women have chronic diseases, 64% do not use medication. The most used medication, among those who use medication, is the hormone 22.7%. Of the 111 participants, 27.0% developed anxiety. In addition, 85.6% received information before the Climacteric/Menopause. In 50.5% of them, the perception of climacteric/menopause is negative. The most common symptoms in perimenopause were: irritability (83.8%), loss of sexual interest (83.8%), physical fatigue or lack of energy (83.8%), tension or nervousness (82.9%), hot flashes (82.9%), pain in muscles and joints (82.0%) difficulty sleeping (73.0%), difficulty concentrating (72.1%), excitability (71.2%) , loss of interest in many things (70.3%). In post-menopausal women, symptoms of shortness of breath and heat were more frequent 73.9%, sleep problems 79.3%, muscle and joint problems 79.3%, physical and mental exhaustion and decreased performance 78.4%, irritability 76.6%, sexual problems 82.9% and vaginal dryness 73%. Regarding quality of life, it was noticed that the most affected domains during the climacteric/menopause period were the environmental (73.28%) and social relationships (66.52%). Finally, a website was built whose format includes spaces for information, support and social interaction on climacteric, menopause, aging and quality of life. Conclusion: Climacteric and menopause symptoms impact women's quality of life. The lack of preparation to face this stage of life can intensify the negative effects that interfere in the female psychosocial context, which are expressed in the development of mental pathologies, dysfunction in the family and social system, and sexual satisfaction. With this in mind, the construction of a website presents itself as an instrument for promoting information and social interaction around this theme, with a focus on facilitating support for better coping with menopause and the female aging process.